Impairment of Renal Function in Eclampsia (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: Aim of the study is to identify changes that occur in renal function in eclampsia patients and to determine the effect of impaired renal function on pregnancy outcome Materials and Methods: This cross-sectional study on the impairment of renal function in eclamptic patients was carried out in the Eclampsia ward of Dhaka Medical College Hospital from July 2009 to December 2009. Study group comprised of 50 diagnosed cases of eclampsia and 50 patients with uncomplicated pregnancy was taken as control. Results: In this study 30% of the eclamptic patients were found to have impairment of renal function. Incidence of impaired renal function was significantly increased among the patients > 25 years of age. Multigravida eclamptic patients were found to be more prone to develop impaired renal function compared to primigravida patients. Blood pressure was significantly increased and platelet count was significantly low in the impaired renal function group of eclamptic patients compared to the normal renal function group. Incidence of foetal complications was significantly higher among the patients with impaired renal function. The eclamptic patients who had proteinuria of >1 gm in 24 hours had more foetal complications than those who had protienuria of